Zapped: A Typology Of Use And Misuse Of The Taser - Upton, Lindsey L. (2011)
Police use of TASER force is currently a hot topic of controversy in the intersections of society and the criminal justice system. Proponents, including manufacturers and law enforcement, value the TASER as a less than lethal alternative to deadly force; providing increased safety for officers as an aid to maintain distance between potentially threatening suspect(s) and officer(s) while preserving the life and well being of suspects in such encounters. Civil and human rights advocacies argue the TASER to be associated with many deaths, serious injury and abuse of power by law enforcement. Those who lean more toward the opposition of the TASER argue it is being abused and misused by law enforcement, resulting in cases of excessive force and wrongful death. The controversy surrounding TASER use of force has received a great deal of media attention; fueling the fire on both sides of the TASER controversy. Manufacturers, law enforcement and other proponents often argue the level of force to be justified and in line with policy while opponents claim excessive force, and occasionally wrongful death, in association with identical cases being justified by police and their departments. It is apparent that much research is needed in this area to gain general knowledge in the reality of TASER use and misuse to positively influence TASER policy in departments across the U.S. Just as a wide array of terms are used to reference the TASER in literature and in the field (Taser, ECD, ECW, CED, etc.), it is a research endeavor to explore if the same ambiguity in terminology is reflective of the TASER practice and policy used in the U.S. criminal justice system. The purpose of this thesis study was to examine and identify police officer prescribed and proscribed TASER use of force. The study is a content analysis of secondary data collection that included articles collected from a National Police Misconduct Statistics and Reporting Project (NPMSRP) website, InjusticeEverywhere.com. Data were examined to identifying common prescribed and proscribed use of force themes in accordance to the 9th Circuit Court of Appeals ruling (Bryan v. MacPherson, 2010). This paper extends knowledge and understanding of current themes of prescribed and proscribed TASER use of force by law enforcement agencies. One-hundred thirteen cases were collected and supplemented with additional resources as they became available. This includes, and is not limited to, non-duplicated online news articles and available court case rulings pertaining to each subject/case. The research was used to create a typology of use of TASER force. The author is not determining the appropriateness of each use of TASER force instance; rather the author provided a contribution to the knowledge base and categorization guideline for future police departments, policy makers, etc. to analyze their own trending , which is strongly encouraged by PERF (Police Executive Research Forum, 2010). While it is important to explore TASER associated fatalities, health consequences, and potential risks with its use, it is also important for police organizations and researchers to conduct simultaneous research on use and misuse of the TASER to its near entirety. Continued evaluations of its use and misuse by law enforcement agencies will aid in evaluations of policy, training, education and practice